Evaluation methods for explosive power and speed endurance for alpine skiers - Hoshino, H.; Tsunoda, K.; Sasaki, T.; Takeda, H. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2014)
Alpine skiers utilize various fitness factors: anaerobic aerobic capacity, isometric and isotonic muscle strength, balance ability, agility other than explosive strength power, and speed endurance capability (Bosco C 1997). In this study, the explosive power and speed endurance of alpine skiers were examined utilizing squat jumps with various loads.